A Fuzzy-Weighted Approach to the Problem of Selecting the Right Strategy Using the Robustness Analysis (Case Study: Iran Automotive Industry). Issue 1 (2nd January 2019) - Sorourkhah, Ali; Babaie-Kafaki, Saman; Azar, Adel; Shafiei Nikabadi, Mohsen
Abstract : Purpose : We focus on a fuzzy-weighted approach to the robustness analysis based on experts' opinions for selecting a reasonable strategy in a special decision-making problem. Design/methodology/approach : We deal with environmental uncertainty by reviewing performance of the strategies among the alternative futures, to answer some complexities of the strategy selection problem by considering the desired number of scenarios, indicators and options as well as collecting experts' judgments in an appropriate time. Weights of the indicators determining the situations of future scenarios are considered as triangular fuzzy numbers. Also, we use the well-known Dolan-Moré performance profile in order to more precisely investigate the strategies situations, especially when their robustness levels are close to each other. Findings : According to the results, concerning environmental situations as well as the possible future of the automotive industry of Iran, the defensive strategy is a robust decision. Among the sub-strategies related to the main strategy defensive, retrenchment and divestiture strategies have a higher robustness level. Originality/value : Using matrix modeling, it is possible to overcome some of the weaknesses of the classical robustness analysis related to reviewing few scenarios, indicators and options as well as the time-consuming process of collecting the experts' opinions.